2000
DOI: 10.1007/bf02492821
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of experimental conditions influencing the surface-enhanced Raman spectroscopic (SERS) detection of substances separated by layer liquid chromatographic techniques

Abstract: SummarySurface-enhanced Raman spectra (SERS) of p-dimethylaminobenzylidenerhodanine have been recorded on silica gel 60 F254 and Si60 F254 Raman TLC plates. Spectra were enhanced by use of a silver sol prepared according to the modified Lee-Meisel procedure. The standard deviations of the intensities and the band ratios for the seven most intense peaks were calculated for 30 parallel measurements. Although the Raman plate gives more reproducible results, several experimental difficulties are encountered in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The first experiments indicate that analyte confirmation can be achieved down to a few pmoles deposited on the TLC plate. This is of marked interest, since TLC -SER(R)S has received much attention in the literature (see e. g. [17]). Generally speaking, the robustness of the set-up was found to be satisfactory throughout the 5-month duration of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The first experiments indicate that analyte confirmation can be achieved down to a few pmoles deposited on the TLC plate. This is of marked interest, since TLC -SER(R)S has received much attention in the literature (see e. g. [17]). Generally speaking, the robustness of the set-up was found to be satisfactory throughout the 5-month duration of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Using citrate-reduced silver colloids, which had been pre-aggregated through the addition of sodium perchlorate, the authors were able to record clear micro-FT SERS spectra of the carotenoid, crocetin, at 10 −5 M concentration and calculated that this corresponded to an analysed mass of 0.02 fg [27]. Other experimental factors, including the choice of metal used for the SERS surface, development method and laser excitation wavelength, that affect the success of TLC-SERS measurements have been discussed in more detail by Kocsis et al [28] and Horvarth et al [29].…”
Section: Sers and Thin Layer Chromatography (Tlc)mentioning
confidence: 96%
“…Methods for silica gel layer preactivation include dipping the plate into a solution of silver oxalate and subsequently pyrolyzing it to form silver particles on the layer (210), vacuum evaporation (211), and citrate reduction (212). It was found that the type of plate and the development procedure (traditional vs. OPLC) influenced significantly the quality of SERS spectra obtained (213). NIR-SERS was shown to be useful for both qualitative and quantitative analysis in a single step (214).…”
Section: B Qualitative Identification Of Zonesmentioning
confidence: 97%